PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN PALMERAH KOTA ADMINISTRASI JAKARTA BARAT - Syauqi Ahmad (Jurnal Renaissance, 2019)
The phenomenon that made the object of research is The Performance of Palmerah City District Administration Staff of West Jakarta. The objectives of the study were (1) To Discuss the influence of the influence of Leadership Style on the Performance of Employees at Palmerah Sub-district Office; (2) Discusses the influence of Discipline on Employee Performance at Palmerah Sub-district Office; And (3) Discusses the influence of Leadership and Discipline Style on Employee Performance at Palmerah Sub-district Office. The research method used is quantitative method. The data were collected by literature study, questionnaire and survey. The sample determination was 72 respondents using total sampling. Based on the discussion of the research results obtained conclusions, namely: (1) There is influence of leadership style on the performance Palmerah Subdistrict employees of 84.9 percent; (2) There is a discipline effect on Palmerah Subdistrict's performance of 78.8 percent; (3) There is influence of leadership style and discipline together to the performance of Palmerah sub-district employees with contribution of influence of leadership style 0,626 bigger than contribution influence of discipline 0,389 to performance of Palmerah Sub-district employees.Keywords : leadership style, discipline and employee performance.